Targeted whole exome sequencing and Drosophila modelling to unveil the molecular basis of primary ovarian insufficiency. Issue 11 (4th September 2021) - Bestetti, I; Barbieri, C; Sironi, A; Specchia, V; Yatsenko, S A; De Donno, M D; Caslini, C; Gentilini, D; Crippa, M; Larizza, L; Marozzi, A; Rajkovic, A; et al.
Abstract: STUDY QUESTION: Can a targeted whole exome sequencing (WES) on a cohort of women showing a primary ovarian insufficiency (POI) phenotype at a young age, combined with a study of copy number variations, identify variants in candidate genes confirming their deleterious effect on ovarian function? SUMMARY ANSWER: This integrated approach has proved effective in identifying novel candidate genes unveiling mechanisms involved in POI pathogenesis. WHAT IS KNOWN ALREADY: POI, a condition occurring in 1% of women under 40 years of age, affects women's fertility leading to a premature loss of ovarian reserve. The genetic causes of POI are highly heterogeneous and several determinants contributing to its prominent oligogenic inheritance pattern still need to be elucidated. STUDY DESIGN, SIZE, DURATION: WES screening for pathogenic variants of 41 Italian women with non-syndromic primary and early secondary amenorrhoea occurring before age 25 was replicated on another 60 POI patients, including 35 French and 25 American women, to reveal statistically significant shared variants. PARTICIPANTS/MATERIALS, SETTING, METHODS: The Italian POI patients' DNA were processed by targeted WES including 542 RefSeq genes expressed or functioning during distinct reproductive or ovarian processes (e.g. DNA repair, meiosis, oocyte maturation, folliculogenesis and menopause). Extremely rare variants were filtered and selected by means of a Fisher Exact test using several publicly available datasets. A case-control Burden test was applied to highlight the most significant genes using two ad-hoc control female cohorts. To support the obtained data, the identified genes were screened on a novel cohort of 60 Caucasian POI patients and the same case-control analysis was carried out. Comparative analysis of the human identified genes was performed on mouse and Drosophila melanogaster by analysing the orthologous genes in their ovarian phenotype, and two of the selected genes were fruit fly modelled to explore their role in fertility. MAIN RESULTS AND THE ROLE OF CHANCE: The filtering steps applied to search for extremely rare pathogenic variants in the Italian cohort revealed 64 validated single-nucleotide variants/Indels in 59 genes in 30 out of 41 screened women. Burden test analysis highlighted 13 ovarian genes as being the most enriched and significant. To validate these findings, filtering steps and Burden analysis on the second cohort of Caucasian patients yielded 11 significantly enriched genes. Among them, AFP, DMRT3, MOV10, FYN and MYC were significant in both patient cohorts and hence were considered strong candidates for POI. Mouse and Drosophila comparative analysis evaluated a conserved role through the evolution of several candidates, and functional studies using a Drosophila model, when applicable, supported the conserved role of the MOV10 armitage and DMRT3 dmrt93B orthologues in female fertility. LARGE SCALE DATA: The datasets for the Italian cohort generated during the current study are publicly available at ClinVar database (http://www.ncbi.nlm.nih.gov/clinvar/ ): accession numbers SCV001364312 to SCV001364375. LIMITATIONS, REASONS FOR CAUTION: This is a targeted WES analysis hunting variants in candidate genes previously identified by different genomic approaches. For most of the investigated sporadic cases, we could not track the parental inheritance, due to unavailability of the parents' DNA samples; in addition, we might have overlooked additional rare variants in novel candidate POI genes extracted from the exome data. On the contrary, we might have considered some inherited variants whose clinical significance is uncertain and might not be causative for the patients' phenotype. Additionally, as regards the Drosophila model, it will be extremely important in the future to have more mutants or RNAi strains available for each candidate gene in order to validate their role in POI pathogenesis. WIDER IMPLICATIONS OF THE FINDINGS: The genomic, statistical, comparative and functional approaches integrated in our study convincingly support the extremely heterogeneous oligogenic nature of POI, and confirm the maintenance across the evolution of some key genes safeguarding fertility and successful reproduction. Two principal classes of genes were identified: (i) genes primarily involved in meiosis, namely in synaptonemal complex formation, asymmetric division and oocyte maturation and (ii) genes safeguarding cell maintenance (piRNA and DNA repair pathways). STUDY FUNDING/COMPETING INTEREST(S): This work was supported by Italian Ministry of Health grants 'Ricerca Corrente' (08C621_2016 and 08C924_2019) provided to IRCCS Istituto Auxologico Italiano, and by 'Piano Sostegno alla Ricerca' (PSR2020_FINELLI_LINEA_B) provided by the University of Milan; M.P.B. was supported by Telethon-Italy (grant number GG14181). There are no conflicts of interest.